VIII Scientific Wallace Conference Proceedings - Martínez Salinas, Alejandra (CATIE- Centro Agronómico Tropical de Investigación y Enseñanza, 2024)
From May 31 to June 3, 2023, CATIE and partners hosted the VIII Scientific Wallace Conference, part of a series initiated in 2002 for in-depth discussions on science and technology strategies related to agriculture, natural resources, and biodiversity conservation in the tropics. The conference focused on the pivotal theme of transforming food systems in LAC. Delving into six thematic areas, participants examined both opportunities and challenges encountered by LAC’s food systems. This document provides a compilation of the submitted abstracts and a summarized versions of keynote speeches. Its primary aim is to contribute to the dissemination of the knowledge and research shared within the framework of the conference.